Adensamento e verticalização em Goiânia nos planos diretores (1968-2007) - Bellorio, Grazielli Bruno (2013)
This research deals with the evolution of the process of uprighting Goiânia. Based on the Master Plan for the period 1968 to 2007, investigated the relationship between economic development and the dynamic process of vertical integration, clearly showing the inducing agents. The study has as its object of study: the master plans drawn up in the late 1960s by architect Jorge Wilheim, the syndication company Serete; Master Plan 1992, prepared by Engevix, the current 2007 plan, drawn up by experts in the City Goiânia, and other laws that deal with the use and occupation of land for the vertical city. Besides the content of each plan, brake in pieces the process of work, until the implementation of the draft bill and its approval. To put these plans within urban site (Goiânia) national and presents a discussion on the local situation, to open a discussion on a new plan. To organize this work, we chose to follow timeframes according to phase of urban expansion of Goiânia and finally the two plans, most of them executed. Served as sources, besides the bibliography, legislation, old photos of the city and zoning maps with the help of GIS. Based on the data obtained, it was revealed that areas intended for uprighting were almost always the same, which contributed to a kind of a big "toothpicks" in certain places because of zoning. We conclude that the current plan for the encouragement of vertical integration in the outlying areas and the linear axes of development.